Case study on crowdfunding - Robano, Virginia (Paris, 2018)
"The present report is a case study on crowdfunding as a finance instrument for SMEs and entrepreneurs. The report aims to examine the characteristics, diffusion and uptake by new firms and existing SMEs, assessing its effectiveness in supporting innovative or potentially high-growth firms to overcome financial constraints; to evaluate what contextual factors can improve or hamper SME access to crowdfunding opportunities; to illustrate policy experiences and programme outcomes; and to identify good practices that promote the broader use of this financing technique."